Bob Dylan, don't look back [videorecording (DVD)] - Pennebaker, D. A.; Dylan, Bob, 1941-; Grossman, Albert; Neuwirth, Bob; Baez, Joan; Price, Alan, 1941- (Distributed by New Video Group, 2007)
Portrait of the artist as a young man. In spring, 1965, Bob Dylan a 23 year-old, pixyish troubadour, spent three weeks in England. Follows him from airport to hall, from hotel room to public house, from conversation to concert. Joan Baez and Donovan, among others, are on hand. It's the period when Dylan is shifting from acoustic to electric, a transition that not all fans, including Baez, applaud. From the opening sequence Dylan is playful and enigmatic.